Estudo de métodos empregando HPLC-DAD e LC-MS/MS para a determinação de resíduos de herbicidas em água e solo do cultivo de arroz irrigado - Gonçalves, Fabio Ferreira (2007)
The irrigated agriculture of Rio Grande do Sul (RS) it is responsible for about 50% of the Brazilian production of rice, and the success of the production depends, generally, of the application of chemical substances. Many of the cultivated areas are infested with red rice, which cause damages in the production and commercialization of the grains. In this sense, it was developed to cultivate that was adapted to the cultivation of tolerant irrigated rice to the imidazolinones herbicides used for the control of the red rice. The cultivation of irrigated rice generates a great impact to the environment, so much in amount as in the quality of the waters. In this work it was developed and validated a method for determination, in waters and soils, of clomazone, imazapic and imazethapyr herbicides residues. They were analysed for HPLC-DAD, being used mobile phase of acetonitrile:water and stationary phase C18 and for the soil samples it was made the confirmation by LC-MS/MS, with ionization electrospray in the way ESI+ mode. For pre-concentration of the samples SPE was used with cartridges C18. The herbicides were eluated with dichlorometane:methanol, and for extraction in the soils was used solvent and ultrasonic bath. The parameters of validation of the method include analytical curve, linearity, limit of detection (LOD), limit of quantification (LOQ), precision and accuracy (recovery). Whole the analytical curves presented larger values of r2 more than 0.99. The LOQs for the method, considering the stage of pre-concentration of 200 times, were 0.12 μg L-1 for the imazethapyr and imazapic herbicides and 0.25 μg L-1 for the clomazone in samples of water. For the soil samples the values of LOQ were of 2.5 μg kg-1 for imazethapyr and imazapic and 5.0 μg kg-1 for clomazone by HPLC-DAD. The values of LOQ for the soil samples for the system LC-MS/MS was 25.0 ng kg-1. The recoveries were between 80.9 and 106.7%, with RSDs smaller than 9.0% for the samples of water and recoveries between 89.3 and 105.7% with smaller RSDs than 8.7% for soil samples. The method was applied in dissipation studies in the irrigated rice and in the determination of the residual concentration in soil samples, where were applied the herbicides, in the crops of 2004/05, 2005/06 and 2006/07. They were found imazethapyr residues at the most 28 days and of the imazapic 21 days after application and the clomazone until 42 days after application of the products in samples of water. In the soil samples were found imazethapyr residues and imazapic in different collected depths.